THE EFFECT OF LACK OF SUPERVISION ON THE DANGER OF BULLYING AT THE HOUSE FOR ORPHANTS AND DHUAFA AULIA PONDOK PETIR BOJONGSARI DEPOK - Apriansyah, Muger; Syahnego, Syahnego; Irawati, Laila (International Journal of Engagement and Empowerment (IJE2), 2024)
An orphanage is a social institution that provides protection, care and education for children who are neglected, orphaned or do not have families who are able to care for them. The background to the establishment of an orphanage is closely related to various social, economic and cultural factors that exist in society. Overall, the background to the establishment of orphanages involves a combination of complex social, economic, cultural and policy factors. Although the main goal is to provide protection and education for children in need, challenges and changes in society continue to influence the role and function of orphanages in responding to the needs of neglected children. However​ at the orphanage care sometimes Where does the problem of bullying occur ? matter the is a serious situation and can impact the emotional and mental well-being of the children living there. Method used​ in activity devotion public This is with give training and socialization To use build pattern think and be enthusiastic children House For understand and can " fight" bullying. Steps taken​ in activity This is : Stage preparation and stages training. Result of devotion to society obtained​ is enhancement understanding and knowledge of the participants House orphans and poor people Aulia Cottage Lightning Bojongsari Depok to be trained and added outlook the importance of, speaking, conveying and fighting If bullying occurs​ children orphanage, and also share administrator House For increase supervision, giving training to staff about recognition and handling bullying, strengthening connection positive between children, and create supportive environment​ for all residents House upbringing. Besides That 's also important for give support emotional and counseling to children who are victims of bullying so that they can recover from impact possibly traumatic​ they experience. for the future and development generation gold in the future​ come